Toxicity and Residual Activity of Insecticides against Diadegma insulare, a Parasitoid of the Diamondback Moth - Daniel Ramírez-Cerón; Esteban Rodríguez-Leyva; J. Refugio Lomeli-Flores; Lauro Soto-Rojas; Samuel Ramírez-Alarcón; Antonio Segura-Miranda (Insects, 2022)
Plutella xylostella is the main pest of cruciferous crops worldwide. To reduce P. xylostella populations, better integration of natural control and chemical control (dominant tactic used) is needed. This work analyzed the compatibility of nine insecticides with the parasitoid Diadegma insulare, outlining them as complementary tools in an integrated pest management strategy. The acute toxicity of spinosad, imidacloprid, indoxacarb, flonicamid, naled, pyridalyl, emamectin benzoate, and spinetoram against the parasitoid was assessed. Residual activity (persistence) was also evaluated over time; the mortality of the parasitoid in contact with leaf tissue of plants treated with insecticides was analyzed. According to the International Organization of Biological Control, all nine insecticides were toxic to D. insulare; the lowest mortality was recorded with spirotetramat (64%) and pyridalyl (48%), while the rest of the insecticides caused 100% mortality at 72 h after application. In terms of persistence, by days 14, 16, 16, 17, 17, 21, and 22 after application, flonicamid, naled, spirotetramat, spinosad, piridalyl, imidacloprid, and indoxacarb caused mortality of less than 25%, respectively, so they were considered harmless (Category 1). Nonetheless, some insecticide toxicity and residual activity must be regarded within integrated pest management programs for conserving the role of D. insulare field populations.